A Contribution to the Knowledge of Vascular Flora of the Site of Biological and Ecological Interest of Kharouba in the Central Plateau of Morocco - Dallahi Youssef; El Aboudi Ahmed; Aafi Abderrahman (European Scientific Journal, ESJ, 2016)
The current study aims to quantify and evaluate the Tetraclinis stands (Tetraclinis articulata (Vahl.) Masters) richness and floristic diversity at Kharouba Site of Biological and Ecological Interest (SBEI). The 150 floristic surveys conducted in the site allowed us to inventory 143 species distinguished with rare taxa majority that are distributed over 54 families and 123 genera. This reduced number of taxa reflects the alarming biodiversity deterioration of the SBEI. The study also enabled us to define the biological spectrum of the study area that is characterized by a significant abundance of Therophytes.